Інтерактивна інформаційна система для підтримки вивчення іноземної мови - Чорний, Владислав; Заболотня, Тетяна (Видавництво Львівської політехніки, 2016)
This article focuses on the creation of a software product (consisting of a website and a browser extension) that will help foreign language learners to find content suitable to their current vocabulary and personal tastes.
Keywords: іноземна мова; мотивація; словниковий запас; медіа-матеріали; веб-сайт; додаток для браузеру; частотний словник